Sistemática e filogenia do fungo parasita Escovopsis associado às formigas Attini - Meirelles, Lucas Andrade [UNESP] (2015)
Attine ant nests harbor a diverse and complex microbiota. Such insects have a mutualistic relationship with mutualistic fungus, cultured as food source. However, several microorganisms are also present in attine nests. Within this microbiota, fungi in the genus Escovopsis are considered specific parasites of the mutualistic fungus. Escovopsis is only reported associated with attine ant nests. Furthermore, this parasite coevolved with attine ants and their mutualistic fungi in a tripartite relationship (tripartite coevolution model). Although several studies aimed to understand the genetic diversity of Escovopsis in Central America (mostly Panama), no comprehensive reports considering large Escovopsis samples are known from South America. There is also few taxonomic work onr this fungus; as a result, after two decades of the description of the first species, up to the present work, only six Escovopsis species have been formally described. In this study, we investigated the systematics, phylogeny and evolution of Escovopsis and separated our results in two chapters. In the first part, we describe a new species, E. kreiselii, first species belonging to basal attine ants. We also discuss the evolution of Escovopsis, indicating a correlation between phylogeny and morphological characters, where less derived strains shows absence of vesicles (structures supporting spore bearing-cells). In the second chapter, we exploit the phylogenetic diversity of Escovopsis associated with higher-attine ants in different countries of the American continent, especially Brazil. Contrary to previous resports, we show that higher attine ants share Escovopsis infections, indicating no strict co-cladogenesis between ant-cultivar-Escovopsis. The description of a new species and the extensive Escovopsis phylogeny presented here provide a first step towards a better understanding of the evolution and taxonomy of this group of fungi, which has potential for biological ...